Smart antenna for RFID applications - Reis, Helder Vasconcelos Graça (2014)
The adoption and proliferation of information systems in many business and personal activities leads to the need of tagging and tracking items and services. Radio frequency identi cation (RFID) systems were developed as an e ort to answer the increasing needs of particulars and enterprises alike for wireless identi cation of objects and data exchange services, enabling a large number of businesses to reduce costs and increase revenue. As to further develop the e ciency provided by businesses worldwide, smart antenna systems were introduced as core component in their production and service providing lines, opening the path for innovative and robust wireless RFID based communication schemes, providing advanced signal capturing, processing characteristics and enhanced tracking and process automation. Smart antennas can be installed within RFID readers, enabling them to more e ciently process returned echoes by the tags and therefore improving the identi cation mechanism. RFID reader architectures with an embedded smart antenna network reliably improve the throughput, the reading speed and position detection of tagged items. A smart antenna based circuit is proposed here for RFID assisted localization and for beam steering applications using a uniform linear array of microstrip directional antennas. Several beamforming and direction of arrival estimation methods were employed in order to analyze their performance and resolution based on the computational load, modulation, and the overall environment in which the smart anetnna system may be deployed.